2020
DOI: 10.1177/1526602820913888
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Appearance of Hybrid FDG–Positron Emission Tomography/Computed Tomography Imaging Following Uncomplicated Endovascular Aneurysm Sealing Using the Nellix Endoprosthesis

Abstract: Purpose: To investigate the physiological uptake of hybrid fluorine-18-fluorodeoxyglucose (FDG)–positron emission tomography/computed tomography (PET/CT) before and after an uncomplicated endovascular aneurysm sealing (EVAS) procedure as a possible tool to diagnose EVAS graft infection and differentiate from postimplantation syndrome. Materials and Methods: Eight consecutive male patients (median age 78 years) scheduled for elective EVAS were included in the prospective study ( ClinicalTrials.gov identifier NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This is because they are difficult to interpret due to false positives from low-grade inflammation associated with prosthetic grafts (17) . Recent work by Jebbink et al (4) , however, suggests this may be different for the Nellix graft. They found decreased FDG uptake at six weeks post-deployment in non-infected Nellix stent-grafts and suggests early inflammation may be less of an issue compared to EVAR.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is because they are difficult to interpret due to false positives from low-grade inflammation associated with prosthetic grafts (17) . Recent work by Jebbink et al (4) , however, suggests this may be different for the Nellix graft. They found decreased FDG uptake at six weeks post-deployment in non-infected Nellix stent-grafts and suggests early inflammation may be less of an issue compared to EVAR.…”
Section: Discussionmentioning
confidence: 97%
“…This aims to mitigate Type-2 endoleak that are associated with late failures with EVAR (2) . Endograft infections are rare but life-threatening complications with an incidence of 0.2-0.7% and mortality rates up to 50% (3,4) . Incidence rates of 0.6-1.2% have been reported for Nellix stent-grafts (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic graft infection (AGI) can occur when microorganism colonization develops in a primary prosthesis following open surgical reconstruction or an endovascular aortic repair (EVAR) [ 24 ]. Although it is a late, rare complication with an incidence ranging from 0.16% to 0.77%, this is a life-threatening condition with a mortality rate of 18-50% [ 25 ].…”
Section: Prosthetic Aortic Graft Infectionmentioning
confidence: 99%
“…In a prospective study by Groot Jebbink et al comparing [ 18 F]FDG PET/CT before and 6 weeks after uncomplicated endovascular aneurysm sealing (EVAS), the homogenous uptake pattern, SUVmax, and TBR were stable before and after the procedure [32]. Marie et al reported no increased [ 18 F]FDG uptake 1 month after EVAR compared with the [ 18 F]FDG uptake before the procedure [33].…”
Section: Literature Reviewmentioning
confidence: 99%